Crochet Garlands: Exploring Communication Design Through Creative Practice to Foster Meaningful Relationships - Vongsakulkasem, Kevalin (Auckland University of Technology, 2025)
This practice-led research asks: How can crochet be utilised as a creative practice with communication design tools to capture and foster meaningful connections? Drawing on the researcher’s personal experience and observation from the past and present, this project investigates the values and qualities of the people in her community. These values and qualities are expressed through พวงมาลัย (Phuang malai), Thai flower garlands, accompanied by a publication that conveys the essence of the entire project. The practice is informed by initiatives like the cultural significance of Thai gift-giving and garlands to create a personal connection to the researcher’s background. Gift-giving is also used as a relational gesture to foster and facilitate meaningful connections through the crocheted garlands. This process is also captured through a visual narrative that showcases the researcher’s navigation between two cultural worlds. The study contributes to the understanding of how crochet can be employed to navigate cultural adaptation.